Pelvic Incidence is Not Constant. Issue 1 (April 2016) - Tammam, Hamdy; Mostafa, Amer; Gad, Wael; Koptan, Wael; El-Sharkawi, Mohammad
Introduction: The pelvis is a very important component in the overall balance. It changes its orientation in space aiming at compensation for any sagittal imbalance. Three pelvic parameters were recognized as descriptive tools for pelvic status. Pelvic incidence (PI) is considered as a constant value after maturity which changes only in pelvic trauma. This work aims to evaluate if the surgical correction of the fixed sagittal imbalance has any effect on the pelvic incidence. Patients and Methods: Twenty seven cases with fixed sagittal imbalance were corrected surgically by posterior spinal osteotomies and prospectively followed for at least one year. Pelvic Incidence (PI), Sacral Slope (SS), Pelvic Tilt (PT), Lumbar Lordosis (LL), Thoracic Kyphosis (TK) and Sagittal Vertical Axis (SVA) were compared between preoperative, postoperative and last follow up long standing lateral whole spine radiographs. Measurements were taken by three experienced spine surgeons independently. Results: Twenty four cases were included, half of them were males, and the mean age was 16.3 (5–46) years. PI was fixed or changed by five degrees or less in seventeen cases (70%). PI increased in four patients (16%) by more than five degrees and decreased by more than five degrees in three cases (12, 5%). The mean increase in the PI was 11.75° (6–20°) and 11.2° (7–23°) postoperatively and at last follow up respectively. Conclusions: Despite that the PI is fixed or minimally changes (five degrees or less) in most of the cases of surgically corrected fixed sagittal imbalance, it is increased in some patients and decreased in others. The long term effect of this observation and its implication on surgical planning is yet to be determined.